EFFICIENT SYNTHESIS AND DIRECTION OF METHYLATION OF 2-METHYLQUINAZOLINE-4-THIONE (Academia Science Repository, 2023)
The alkylation reaction of 2-Methylquinazolin-4-one with methyl iodide and dimethylsulfate in alcohol was studied. When aprotic dipolar DMFA is used as a solvent and used as a methylating agent, 1,3-dimethylquinazolin-4-one is also formed along with this compound.